2009
DOI: 10.1177/0267658309104578
|View full text |Cite
|
Sign up to set email alerts
|

Processability Theory and the role of morphology in English as a second language development: a longitudinal study

Abstract: This article tests a prediction made by Processability Theory (Pienemann, 1998; 2005) that morphological acquisition is the driving force in English as a second language (ESL) development. It first outlines the model of psycholinguistic processing assumed by Processability Theory and shows how stages fall out from it. It then presents the hypothesis that morphological information propels development before sentence-level processing at stage 5 and describes what this should predict for ESL learners. A study is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 4 publications
(1 reference statement)
6
40
0
1
Order By: Relevance
“…This study found that one participant acquired the predicted syntax at stages 3e4 without the predicted morphology while the other participant developed the syntax driven by morphology following PT. Dyson's (2009) findings suggested that ESL learners may not distinguish functional categories from lexical categories and that syntax and morphology may develop independently of each other. L1 transfer to L2 acquisition has also been discussed in recent empirical studies.…”
Section: Empirical Studies Testing Pt Predictionmentioning
confidence: 97%
See 4 more Smart Citations
“…This study found that one participant acquired the predicted syntax at stages 3e4 without the predicted morphology while the other participant developed the syntax driven by morphology following PT. Dyson's (2009) findings suggested that ESL learners may not distinguish functional categories from lexical categories and that syntax and morphology may develop independently of each other. L1 transfer to L2 acquisition has also been discussed in recent empirical studies.…”
Section: Empirical Studies Testing Pt Predictionmentioning
confidence: 97%
“…However, the latest PT publications have explicitly hypothesized that the development of syntax and morphology has two separate motivations (Di Biase & Kawaguchi, 2013;Pienemann & Kebler, 2012;Yamaguchi, 2013). In this context, recent cross-sectional and longitudinal studies on English L2 learners have demonstrated the effects of L1 influence and individual variation on morphological development (Charters, Dao, & Jansen, 2011;Dao, 2007;Dyson, 2009;Zhang & Widyastuti, 2010). Meanwhile, other longitudinal child L2 studies have confirmed PT prediction (Yamaguchi, 2013;Yamaguchi & Kawaguchi, 2014).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations